Spider (Araneae) from West Greenland. - Holm, Åke (Meddelelser om Grønland, 1967)
The spider fauna of West Greenland has been the subject of an investigation based up on a material of spiders collected by the author mainly in the Godthab area and in Disko. Most of the material was collected by means of sifting and with pitfall traps. A list of 50 West Greenland species of spiders is given with notes on their taxonomy, ecology, and distribution. In a table 64 species and subspecies of spiders hitherto known from Greenland are listed with particulars about their Arctic distribution. A zoogeographical analysis of the spider fauna of Greenland gave the result that it comprises 41 % Holarctic, 20% Palaearctic, and 39% Nearctic forms and that no difference in this respect exists between East and West Greenland. Three new species has been described, belonging to the genera Sciastes, Praestigia, and Bathyphantes. For the species Typhochrestus borealis JACKS. the new genus Conigerella has been established. Several new synonyms of Greenland spiders have been stated.